Bugs - Mills, Andrea (New York, N.Y. : DK Pub., 2017)
Describes the physical characteristics and behavior of different insects, including how they move, what they eat, and more.
Includes index.
5.1
3-6.
3-6
english
Keywords: Insects -- Juvenile literature; Insects -- Miscellanea -- Juvenile literature; Insects; Insects -- Miscellanea; Insects; Insects -- Miscellanea